PERAN DINAS KOTA SERANG DALAM PEMELIHARAAN ANAK TERLANTAR TAHUN 2021 - Aji Bagus Setiyoko; Alamsyah Basri; Ade Millatus Sa’diyah; Toni Anwar Mahmud; Muhamad Asmawi (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2022)
ABSRACT The Serang City Social Service is one of the government affairs assistance agencies of Serang City which carries out its duties in the social sector. One of his duties is the care of neglected children, which is stated in the 1945 Constitution Article 34 Paragraph 1 which explains that the poor and neglected children are cared for by the state. This study aims to determine the extent to which the maintenance of neglected children is carried out by the city government through the Serang City Social Service in 2021. The method used in this study is a qualitative research where the results of the findings in this study will be analyzed and described in detail and clearly. The year 2021 is a very limited year, both in terms of budget, facilities, and direct implementation. PPKM policies issued by the government have had many impacts on existing government elements and the Serang City Social Service is no exception which has experienced many obstacles in the care of neglected children so that in carrying out its role as an authorized institution in the care of abandoned children it does not run optimally.